Process study of ceramic membrane-coupled mixed-cell fermentation for the production of adenine - Sun, Pengjie; Li, Changgeng; Gong, Yu; Wang, Jinduo; Xu, Qingyang (Frontiers in Bioengineering and Biotechnology, 2022)
In this study, ceramic membrane-coupled mixed-cell fermentation was used to increase adenine production and reduce the synthesis of by-products. Nucleoside hydrolase (encoded by the Rihc gene) was used to produce adenine by coordinated fermentation with the adenosine-producing bacterium B. subtilis XGL. The adenosine hydrolase (ADH)-expressing strain Escherichia coli BL21-ADH was successfully employed and the highest activity of the crude enzyme solution was found by orthogonal experiments at 170 W power, 42% duty cycle, and 8 minutes of sonication. The highest ADH activity was found after 18 hours of induction incubation. E. coli BL21-ADH was induced for 18 hours and sonicated under the above ultrasonic conditions and the resulting crude enzyme solution was used for co-fermentation of the strain and enzyme. Moreover, 15% (v/v) of the ADH crude enzyme solution was added to fermentation of B. subtilis XGL after 35 hours. Finally, the whole fermentation system was dialyzed using coupled ceramic membranes for 45 and 75 hours, followed by the addition of fresh medium. In contrast, the ADH crude enzyme solution was added after 35, 65, and 90 h of B. subtilis fermentation, with three additions of 15, 15, and 10% of the B. subtilis XGL fermentation system. The process was validated in a 5 L fermenter and 110 ± 2 g of adenine was obtained, with no accumulation of adenosine and D-ribose as by-products. The enzymatic activity of the ADH crude solution treated with ultrasound was greatly improved. It also reduced the cellular activity of E. coli BL21-ADH and reduced effects on bacterial co-fermentation. Membrane-coupled dialysis solved the problem of decreased yield due to poor bacterial survival and decreased viability, and eliminated inhibition of the product synthesis pathway by adenosine. The batch addition of crude enzyme broth allowed the continuous conversion of adenosine to adenine. This production method provides the highest yield of biologically produced adenine reported to date, reduces the cost of adenine production, and has positive implications for the industrial production of adenine by fermentation.